2016
DOI: 10.1016/j.cgh.2015.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Ustekinumab Provides Clinical Benefit for Two-Thirds of Patients With Crohn’s Disease Refractory to Anti–Tumor Necrosis Factor Agents

Abstract: Almost two-thirds of patients with CD refractory to at least 1 anti-TNF agent receive clinical benefit from ustekinumab therapy, not requiring steroids for up to 12 months afterward. While awaiting results from ongoing trials, ustekinumab can be considered for use in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
147
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(161 citation statements)
references
References 25 publications
(25 reference statements)
9
147
1
4
Order By: Relevance
“…In addition, the initial response to ustekinumab and the use of two or more immunosuppressants were found to predict a good response, while previous bowel resection predicted long-term failure with ustekinumab [69]. Another observational study demonstrated that almost two-thirds of patients with CD refractory to at least one anti-TNF agent receiving ustekinumab were able to be free from steroids for up to 12 months [71].…”
Section: Interleukin Inhibitor Ustekinumabmentioning
confidence: 98%
“…In addition, the initial response to ustekinumab and the use of two or more immunosuppressants were found to predict a good response, while previous bowel resection predicted long-term failure with ustekinumab [69]. Another observational study demonstrated that almost two-thirds of patients with CD refractory to at least one anti-TNF agent receiving ustekinumab were able to be free from steroids for up to 12 months [71].…”
Section: Interleukin Inhibitor Ustekinumabmentioning
confidence: 98%
“…Forty-three patients had a clear non-response at 3 months. Out of the 79 patients with a clinical benefit at 3 months, the majority had luminal CD [66] . Only a minority had perianal disease.…”
Section: Anti Il-23 Strategies In Ibdmentioning
confidence: 99%
“…Remission at week 6, however, showed no significant difference between the treatment groups and placebo. As Ustekinumab has been approved as Stelara ® for the treatment for psoriasis, there was a small GETAID study published by Wils et al [66] from Lille about the efficacy and safety of subcutaneous Ustekinumab in refractory CD patients. This was a multicenter retrospective study on off-label use of Ustekinumab in patients with desperate situations [66] .…”
Section: Anti Il-23 Strategies In Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapy with Infliximab (IFX), Adalimumab (ADA) or Certolizumab Pegol (CZP), are antibodies against TNF-α, have demonstrated that it is effective in terms of induction and maintained responses [11][12][13]. Unfortunately, approximately 20-40% of CD patients do not respond to anti-TNF-α therapy and 40% of patients who initially respond lose response [14]. Those who do not respond to the first anti-TNF-α have lower response rates to the second or third with this kind of therapy.…”
Section: Introductionmentioning
confidence: 99%